Lipid characterization of Pleuragramma antarcticum (Nothoteniidae) larvae off East Antarctica (139 degrees E-145.10 degrees E) during summer - Tavernier, Eric; Mayzaud, Patrick; Boutoute, Marc; Vallet, Carole; Koubbi, Philippe (Polar Biology, 2012)
International audience Pleuragramma antarcticum (Antarctic silverfish) larvae are a key component of the neritic assemblages in the Antarctic coastal waters and can be considered as an indicator of the future changes that may occur in this area. Lipid class and fatty acid composition was studied to assess the nutritional status and evaluate the type of dominant trophic interactions of P. antarcticum larvae collected between Terre Ad,lie and the Mertz Glacier Tongue (139A degrees E-145.10A degrees E) during summer 2007. P. antarcticum larvae exhibit moderate lipid levels (11.9-15.0% dry weight). Lipid class analyses showed a similar pattern over the study area consisting mainly of polar lipids (61-75% of total lipids). During their first summer, larvae started to accumulate small amount of lipid reserves in the form of triacylglycerols (10-16% of total lipids). Polar lipids were dominated by phosphatidylcholine (55-59%) followed by phosphatidylethanolamine (19-21%). Fatty acid signature of triacylglycerols indicates (1) a dominance of copepod of the Oithona type in the trophic pattern of P. antarcticum larvae and (2) a significant contribution of phytoplankton. In the same way, the analysis of gut content shows that 70% of larvae fed on various assemblages of phytoplankton and zooplankton (mainly copepods) and 30% of larvae fed exclusively on phytoplankton. Although a carnivorous diet is commonly described, our results suggest that P. antarcticum larvae showed an opportunistic feeding strategy (i.e. high degree of omnivory) and that dietary energy seems to be mainly directed towards fast growth rather than energy storage for periods of starvation.